Methyl 2-[(3,5-di-tert-butyl-4-hydroxybenzyl)sulfanyl]pyridine-3- carboxylate n-hexane hemisolvate - Ariffin, Azhar; Ng, S.W.; Nordin, N.; Yehye, W.A. (International Union of Crystallography, 2012)
The title solvated ester, C22H29NO 3S·0.5C6H14, crystallizes with two independent molecules along with a hexane molecule in the asymmetric unit. The two aromatic rings are separated by an -CH2-S- linkage; the rings are aligned at 83.27 (4)°in one molecule and 47.66 (7)°in the other. The hydroxy group of one molecule forms an O - H⋯O hydrogen bond to the other molecule.